1997
DOI: 10.1046/j.1472-765x.1997.00067.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Escherichia coli O157 : H7 in yoghurt during preparation and storage at 4°C

Abstract: S . M AS S A, C. A LT IE R I, V. Q UA RA N TA AN D R. DE P AC E. 1997. Cow's milk was inoculated with ca 10 3 and 10 7 cfu ml −1 Escherichia coli O157 : H7. After fermentation at 42°C for 0-5 h, the yoghurt was stored at 4°C. Two kinds of yoghurt were used : traditional yoghurt (TY), made with Streptococcus thermophilus and Lactobacillus bulgaricus starter cultures, and 'bifido' yoghurt (BY), made with the two starter cultures plus Bifidobacterium bifidum. After 7 d E. coli O157 : H7 decreased from 3·52 to 2·7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
55
0
6

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 1 publication
7
55
0
6
Order By: Relevance
“…This suggested that the three yogurt flavors had no effect on the microbial counts. However, Massa, Altieri, Quaranta, & Pace (1997) and Ogwaro, Gibson, Whitehead, & Hill (2002) detected the counts of E.coli during storage. Benkerroum, Oubel, & Mimoun (2002) also detected the numbers of S. aureus in yogurt product.…”
Section: Microbial Countsmentioning
confidence: 92%
“…This suggested that the three yogurt flavors had no effect on the microbial counts. However, Massa, Altieri, Quaranta, & Pace (1997) and Ogwaro, Gibson, Whitehead, & Hill (2002) detected the counts of E.coli during storage. Benkerroum, Oubel, & Mimoun (2002) also detected the numbers of S. aureus in yogurt product.…”
Section: Microbial Countsmentioning
confidence: 92%
“…The pathogenic strains were reactivated twice using brain heart infusion (BHI) broth (Difco, 1984) at 37°C for 20-24 hrs before use in this study and were transferred weekly. These organisms were maintained on tryptic soy agar (Massa et al, 1997) and the activating inoculum was prepared after two successive 24-h cultures in tryptic soy broth (TSB) inoculated and incubated at 37°C for 48 hrs.…”
Section: Methodsmentioning
confidence: 99%
“…As regards to the results presented in Table 3 easily observed that, the pH was reduced slightly in the absence of lactic acid bacteria. Massa et al (1997) indicated that Escherichia coli 0157: H7 survived during the fermentation and storage of both traditional and bifido yoghurt and pH levels obtained during fermentation of the two products were within the range that has been demonstrated to allow the survival of Zero 20 19 23 24 17 15 28 30 32 30 12 26 14 29 11 20 3 31 13 51 11 24 32 11 33 7 27 2 37 3 70 5 36 37 7 38 1 32 1 45 1 91 3 48 40 2 44 0 44 1 51 0 113 2 72 41 0 50 0 55 0 70 0 140 0 A = control (SM incoulated with pathogens only), B = The incoculation of lactic acid bacteria and pathogenic organisms is in the same time at zero time. the pathogen.…”
Section: Monocytogenes Escherichia Coli S Aureus S Typhimurium Bmentioning
confidence: 99%
“…Salmonella üzerine s›n›rl› say›da çal›flma olsa da (23) patojen bakterilerin yo¤urdun fermantasyonu s›ras›ndaki canl› kalma durumu birçok araflt›rmac› taraf›ndan incelenmifltir. Çal›flmalar yo¤urdun fermantasyonu s›ras›ndaki pH'n›n patojen bakterilerin (Staphylococcus aureus, E. coli O157:H7) canl› kalmalar›na izin verdi¤ini ve fermantasyonun sonunda, kullan›lan yo¤urt kültürlerinin orijinlerinden ba¤›ms›z (5), son pH de¤erine ba¤l› olarak mikroorganizma say›s›nda sadece hafif bir azalman›n oldu¤unu belirtmifllerdir (7,8). Di¤er taraftan laktik asit bakterileri taraf›ndan üretilen, antimikrobiyel özellik gösteren bakteriyosinler, hidrojen peroksit, etanol, diasetil gibi bileflikler de fermente ürünlerde patojen geliflimi üzerine etki edebilmektedir (24).…”
Section: Sonuç Ve Tartişmaunclassified